Quality of Life Pasien Gagal Ginjal Kronis yang Melakukan Terapi Hemodialisis Rutin - Shahylannanda Tito Yuwono; Gita Sari Aryani; Linda Setyowati; Mega Hasanul Huda; Mohammad Heri Kurniawan; Alfanira Setiawan (Institut Kesehatan Hermina, 2022)
Chronic kidney failure is a progressive and irreversible renal function disorder in which the body's ability to fail to maintain metabolism and fluid and electrolyte balance. Patients undergoing long-term hemodialysis must be faced with various problems such as financial problems, difficulty in maintaining a job, depression and fear of death that affect their quality of life. The purpose of this study was to describe the quality of life of patients with chronic kidney failure undergoing routine hemodialysis therapy at RSHY. The research method is descriptive with a cross sectional approach. The population is 70 patients with chronic renal failure who undergo routine hemodialysis therapy in the Hemodialysis Room RSHY according to the inclusion criteria and exclusion criteria determined by the researcher. The results showed that the quality of life was seen from 4 aspects, namely physical, psychological, social and environmental. From a physical point of view, the majority of 47 (67.1%) have a moderate quality of life. In terms of psychology, the majority there are 50 (71.4%) respondents have a moderate quality of life. From a social perspective, the majority of respondents have a moderate quality of life as many as 47 (67.1%). In terms of the environment, the majority of 36 (51.4%) respondents have a moderate quality of life. The conclusion of this study is that there is a significant difference in the quality of life of younger CKD patients undergoing hemodialysis on the physical aspect. In addition, there were also significant differences in quality of life in patients using HD Cath vascular access on psychological aspects.